The myotomal diwanka (lh3) glycosyltransferase and type XVIII collagen are critical for motor growth cone migration - Schneider, Valerie A; Granato, Michael (Neuron (Cambridge, Mass.), 2006)
The initial migration of motor growth cones from the spinal cord into the periphery requires extrinsic cues, yet their identities are largely unknown. In zebrafish diwanka mutants, motor growth cones are motile but fail to pioneer into the periphery. Here, we report on the positional cloning of diwanka and show that it encodes LH3, a myotomally expressed multifunctional enzyme with lysyl hydroxylase and glycosyltransferase domains. Cloning, expression analysis, and ubiquitous overexpression of other LH family members reveals that only diwanka (lh3) possesses a critical role in growth cone migration. We show that this unique role depends critically on the LH3 glycosyltransferase domain, and provide compelling evidence that diwanka (lh3) acts through myotomal type XVIII collagen, a ligand for neural-receptor protein tyrosine phosphatases that guide motor axons. Together, our results provide the first genetic evidence that glycosyltransferase modifications of the ECM play a critical role during vertebrate motor axon migration.